Talar Osteonecrosis after Subchondroplasty for Acute Lateral Ligament Injuries: A Small Case Series. Issue 4 (22nd October 2020) - Foran, Ian; Bohl, Daniel D.; Vora, Anand M.; Mehraban, Nasima; Hamid, Kamran S.; Lee, Simon
Category: Ankle; Sports; Trauma Introduction/Purpose: Non-operative treatment is regarded as the standard of care for the management of acute, uncomplicated lateral ankle sprains. As diagnostic and treatment options evolve, there is intermittently renewed interest in early surgical treatment of these acute injuries. Wider availability of magnetic resonance imaging (MRI) has made advanced imaging of acute ankle sprains more commonplace. One entity commonly seen on MRI is the 'bone marrow lesion' (BML). Recently, a procedure termed 'Subchondroplasty' (Zimmer, Warsaw, Indiana) has been developed to address chronic bone marrow lesions that have failed conservative management. We present a series of five cases referred from outside institutions in which patients developed rapid osteonecrosis of their tali after undergoing acute lateral ligament reconstruction with talar Subchondroplasty. Methods: We retrospectively evaluated the charts and available imaging of five patients who had developed osteonecrosis after undergoing a Subchondroplasty procedure in the setting of acute lateral ligament injury at outside institutions. Outside radiology reports, x-rays and magnetic resonance images, clinic notes, and operative reports were collected and analyzed. Patient demographics, comorbidities, and secondary interventions (after the index procedure) were recorded. Results: Average patient age was 23 (range 16-31). All patients were healthy. The patients were taken care of by different outside providers. All patients had pre-operative MRI demonstrating ATFL signal changes and bony edema within the talus in a distribution expected after ankle sprain. All patients were taken to the OR within 4 weeks of injury. Three underwent isolated talar Subchondroplasty; two underwent Subchondroplasty and an open Broström procedure. Within 6 months, radiographs and MRI in all patients demonstrated diffuse sclerosis of the tali, and diffuse talar hyperintensity on MRI scans, consistent with osteonecrosis. Two patients additionally had talar fragmentation and collapse. Currently, one patient has subsequently undergone total ankle replacement, two have had arthroscopy with bone marrow stimulation, and two are considering arthrodesis. Conclusion: We present 5 cases from outside institutions in which patients with acute ankle sprains and associated acute talar bone marrow lesions developed osteonecrosis after Subchondroplasty with or without lateral ligament repair. Although Subchondroplasty was likely not well-indicated in these acute cases, it raises a question of whether Subchondroplasty may be harmful to the talar blood supply. There is currently a lack of evidence to support Subchondroplasty for use in the foot and ankle. Practitioners should exercise caution when performing Subchondroplasy for the talus.